Understanding Digital Health Technologies Using Mind Maps. Issue 1 (1st December 2020) - Seckman, Charlotte; Van de Castle, Barbara
Abstract: Purpose: The purpose of this project was to explore digital health technologies in the healthcare environment through the use of concept and mind mapping tools in a graduate level informatics practicum course. Design: This descriptive course evaluation project was conducted at a large university school of nursing during the 2019–2020 academic year and included a convenience sample of 163 doctor of nursing practice students. Methods: Students completed four major deliverables exploring digital health technologies and data sources using mind maps. Project goals were evaluated using detailed rubrics and data from a course evaluation questionnaire (CEQ) then analyzed using descriptive statistics. Comments from the CEQ and reflection documents were reviewed for themes and validated by two experts. Findings: The variety and creativity of the mind maps along with student comments indicated their ability to apply critical thinking skills to the specific content and technologies being examined. Overall CEQ mean scores were high ( M = 4.35), indicating that the mind mapping deliverables were logical, relevant, appropriate, and meaningful to learning. Conclusions: Nurse educators and healthcare professionals should consider using mind mapping techniques because this venue allows for expanded understanding of the complexities of the healthcare environment and integration of related digital health technologies. Clinical Relevance: The recent pandemic highlighted the necessity for new technologies to continue providing patient care services. Mind maps are a fast and economical tool for understanding and prioritizing the needs of an organization as well as a unique teaching strategy to promote critical thinking and sharing of ideas related to digital health technologies.